2007
DOI: 10.1086/510488
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Participants in the Multicenter AIDS Cohort Study and the Women's Interagency HIV Study

Abstract: The characteristics of the men in the MACS who died and women in the WIHS who died differ, as do the risk factors for mortality. These results characterize important target groups for interventions to reduce accident- and injury-related deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 23 publications
2
51
2
3
Order By: Relevance
“…In addition, the Multicenter AIDS Cohort Study and the Women's Interagency HIV Study have shown that higher alcohol use is associated with significantly increased risk for mortality in HIV-positive individuals [56]. Chronic alcohol administration induces increased viral load and accelerated significant and early nutritional, metabolic, and immunologic alterations in HIV-positive animals [57], but the identification of direct toxic effects and the translation of such effects to humans require further investigation.…”
Section: Risky Behaviors: the Hiv Examplementioning
confidence: 99%
“…In addition, the Multicenter AIDS Cohort Study and the Women's Interagency HIV Study have shown that higher alcohol use is associated with significantly increased risk for mortality in HIV-positive individuals [56]. Chronic alcohol administration induces increased viral load and accelerated significant and early nutritional, metabolic, and immunologic alterations in HIV-positive animals [57], but the identification of direct toxic effects and the translation of such effects to humans require further investigation.…”
Section: Risky Behaviors: the Hiv Examplementioning
confidence: 99%
“…Benzer olarak alkol kullanan kişilerde viral yükün saptanamaz hale gelmesi de dört kat yavaş olmaktadır (p=0,04). Literatürde alkol kullanımının virolojik başarısızlık ve CD4 T lenfositlerin sayısında düşüklükle ilişkisini gösteren birçok çalışma bulunmaktadır [35][36][37][38] .…”
Section: Alkolunclassified
“…A Swiss study was excluded because it evaluated social co-factors of HIVnon-progression but not mortality [59]. A cohort study on mortality among HIV-infected participants in the Women's Interagency HIV Study and the Multicenter AIDS Cohort Study were excluded because it focused only on accident-and injury-related deaths [60].…”
Section: Literature Searchmentioning
confidence: 99%